2014
DOI: 10.1289/ehp.1307480
|View full text |Cite
|
Sign up to set email alerts
|

CpG Sites Associated with Cigarette Smoking: Analysis of Epigenome-Wide Data from the Sister Study

Abstract: Background: Smoking increases the risk of many diseases, and it is also linked to blood DNA methylation changes that may be important in disease etiology.Objectives: We sought to identify novel CpG sites associated with cigarette smoking.Methods: We used two epigenome-wide data sets from the Sister Study to identify and confirm CpG sites associated with smoking. One included 908 women with methylation measurements at 27,578 CpG sites using the HumanMethylation27 BeadChip; the other included 200 women with meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
86
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 41 publications
13
86
1
Order By: Relevance
“…The authors show that smoking-associated alterations of a CD3 lymphocyte subtype explain the reports by multiple authors of tobacco-associated DNA methylation alterations at the GPR15 locus. Because it is possible that tobacco smoking activates NK cells, we examined whether the long list of loci reported to have altered methylation associated with smoking 77 might also be found as DMSs indicative of NK activation. We observed that change in methylation of the AHRR locus is both a marker of NK activation and smoking 78 and that several other DMSs associated with NK activation that we found here have been reported by others to be associated with smoking, including: MYO1G (cg07826859), NCF4 (cg02532700), and GPR68 (cg05875421).…”
Section: Implications For Population-based Research and Therapeuticsmentioning
confidence: 99%
“…The authors show that smoking-associated alterations of a CD3 lymphocyte subtype explain the reports by multiple authors of tobacco-associated DNA methylation alterations at the GPR15 locus. Because it is possible that tobacco smoking activates NK cells, we examined whether the long list of loci reported to have altered methylation associated with smoking 77 might also be found as DMSs indicative of NK activation. We observed that change in methylation of the AHRR locus is both a marker of NK activation and smoking 78 and that several other DMSs associated with NK activation that we found here have been reported by others to be associated with smoking, including: MYO1G (cg07826859), NCF4 (cg02532700), and GPR68 (cg05875421).…”
Section: Implications For Population-based Research and Therapeuticsmentioning
confidence: 99%
“…Recent MWAS studies have identified and replicated smoking-related DNAm sites in samples of European ancestry [50, 51, 53]. The most significant smoking-related DNAm sites are hypomethylated among smokers [53, 54, 58]. Several studies also reported an inverse association between pack-years and DNA methylation, and a positive association between time since quitting smoking and DNA methylation [51, 55, 58, 62].…”
Section: Environmental Modifiers Of Dna Methylomementioning
confidence: 99%
“…Smokerelated changes in DNA methylation have also been detected in blood cells [18][19][20][21] and in newborns [37] in recent epigenomewide association studies on DNA methylation and smoking habits. Even though only a relatively low number of CpG sites attained the high statistical significance required to be identified as differently methylated in such untargeted studies, this does not rule out the possibility that smoking could elicit milder effects also in other genes, which may be important when critical genes are affected.…”
Section: Discussionmentioning
confidence: 91%
“…Altered methylation of cancer-related genes is, in fact, frequently observed in lung tumors of smokers [8][9][10][11], and a progressive accumulation of epigenetic alterations is also observed in the respiratory epithelium of cancer-free heavy smokers [12][13][14] and in exfoliated cells of smokers sputum [15]. Moreover, changes in the methylation profile of cancer related genes have been observed in plasma DNA from cancer-free heavy smokers [16,17], and smoking-related changes in methylation at a number of CpG sites have been identified in epigenome-wide investigations in blood cells of subjects with different smoking habits [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%